A Research Study on Islamic Legal Maxims in the context of ‘Climate Resilient Development Pathways’ (CRDPs) - Muhammad Mahmood ul Hassan Shah; Dr. Abdul Ghaffar (Journal of Religion and Society, 2025)
Islamic legal maxims (Al-Qawaid Al-fiqhiyyah) have been extensively extracted from the all-inclusive meanings of shariah. These legal maxims are very important as to encapsulate the Islamic legal philosophy (shariah’s objectives) in a sentence. They are not only capable to assess the data of other discourses in an Islamic legal method they also show the direction to them to the Islamic legal framework. Ergo, ‘how to stop the global climate change’, aka, ‘Climate Resilient Development Pathways’ (CRDPs) are assessed and directed by islamic legal maxims. In this article, it has been tried to apply the Islamic legal maxims to the data of ‘Climate Resilient Development Pathways’ in order to provide the Islamic legal philosophy for the climate science and management. Keywords: Islamic Legal Maxims, CRDPs, Global Climate Change, Climate Science, Islamic Legal philosophy